1996
DOI: 10.2514/3.780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of freestream nonequilibrium on convective heat transfer to a blunt body

Abstract: The axisymmetric Navier-Stokes equations are solved numerically for nonequilibrium airflows over a hemisphere for two sets of conditions. One set corresponds to a wind-tunnel test flow where the freestream is vibrationally excited and dissociated air, and the other corresponds to hypersonic free flight where the freestream is air at atmospheric conditions. Relevant similitude parameters are partially duplicated hi the computations as in the wind-tunnel testing of convective heating. A nonequilibrium formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the current work, the edge of the boundary layer is defined as the location where the total enthalpy is 99 % of the freestream total enthalpy for consistency with Ref. [44,45] who performed a similar analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current work, the edge of the boundary layer is defined as the location where the total enthalpy is 99 % of the freestream total enthalpy for consistency with Ref. [44,45] who performed a similar analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is necessary to resort to thermochemical nonequilibrium Navier-Stokes simulations to answer the abovementioned question. Gökcen [45] presented an investigation of the question by comparing the nonequilibrium stagnation point heat flux computed from two different freestreams with the same total enthalpy but different thermochemical statesone was in equilibrium while the other was frozen at a thermochemical state representative of a nozzle flow in a hypersonic facility. Gökcen showed that for lower total enthalpy conditions around 7 MJ/kg, the nonequilibrium stagnation point heat flux was uninfluenced by the thermochemical state of the freestream provided the total enthalpy was the same.…”
Section: On the Potential Uncertainties Of The Correction Factorsmentioning
confidence: 99%
“…The thermodynamic activities a of the components were calculated from their mole fraction χ by where the thermodynamic activity coefficients χ Wat , γ Met , and γ Tol of methanol, water, or toluene in binary mixtures were evaluated either by the simple one-parameter Margules activity model or by the UNIFAC group contribution method …”
Section: Methodsmentioning
confidence: 99%
“…The one-parameter Margules activity model provides a simplified model of the thermodynamic activity of each component of a binary mixture as a function of its mole fraction. Assuming components of similar size, the model describes the difference in the polarity of the components by a parameter A with A = 0 for components with identical polarity and ideal mixing, 0 < A < 2.45 for nonideal but miscible mixtures, and 2.45 < A for partially miscible components.…”
Section: Methodsmentioning
confidence: 99%